ANALISIS PENERAPAN PSAK NO.45 PADA ORGANISASI NIRLABA (STUDI PADA LEMBAGA MASJID AT-TAQWA, SIDOARJO) - PUTRI, ERIKA; WURYANI, ENI (Jurnal Akuntansi AKUNESA, 2019)
Mosque is one of the non-profit organizations that earns their wealth from donations. The Mosque made its financial statement with the aim of providing information to the donators about the donation they receive. The forming of non-profit organization financial statement in Indonesia is being regulated at SFAS 45. This research was using Qualitative Method research. This study aims to determine the application of SFAS 45 in the At-Taqwa Mosque, and reconstruct the financial report of the At-Taqwa mosque. The managements of At-Taqwa are still not acknowledged about SFAS 45. The institution should start to give a training about the practicing of SFAS 45, therefore the managements can acknowledge the financial reporting which is accordance with the applicable standards in Indonesia for non-profit organization and make the accountable financial report for the organization. Keywords: Mosque, Non-profit Organization, SFAS 45